PERENCANAAN STRUKTUR GEDUNG RUSUNAWA DI KABUPATEN SUKOHARJO DENGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS - Harris Ian Masdhuki; Kusdiman Joko Priyanto; Teguh Yuono; Kukuh Kurniawan Dwi Sungkono; Chia Soi Lee (Journal of Civil Engineering and Infrastructure Technology, 2026)
The rapid population growth in the city of Sukoharjo and the increasing selling value of land, the construction of flats is the fulfillment of the need for housing. "Structure planning of the Eight-storey Rusunawa Building in Sukoharjo Regency aims to plan a high-rise building, which is strong against working loads. The structures reviewed include the upper structure and lower structure. The building structure uses (SRMPK) and shear walls. Calculation of the structural design of the roof slab support and pitch in the x and y direction Ø10 - 140 mm, reinforcement slab slab Ø12 - 170 mm, sloof 50/25 pedestal 4 D 13 mm, pitch 4 D 13 mm, shear Ø8 - 110 mm, main beam 60/30 bearing 6 D 22 mm, pitch 4 D 22 mm, shear Ø10 - 110 mm, joist 40/25 bearing 3 D 13 mm, pitch 3 D 13 mm, shear Ø10 - 110 mm, column 1 90/ 90 main 18 D 25, shear Ø12 - 200 mm, column 2 80/80 main 14 D 25 mm, shear Ø10 - 200 mm, wall shear 250 mm, borepile 70 cm, depth 20 m, studs 4 pieces, main 11 D 22 , shear Ø12 - 120 mm, pilecap 3.5 m/3.5 m, thickness 800 mm, x and y direction D 22 - 120 mm